Improved Dunham coefficients of HCl isotopologues; Proceedings of SPIE; Vol. 10035 : Atmospheric and Ocean Optics: Atmospheric Physics - Velichko T. I. (Molecular Spectroscopy and Atmospheric Radiative Processes, 2016)
Title screen